2019
DOI: 10.1111/evj.13093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different doses of inhaled ciclesonide on lung function, clinical signs related to airflow limitation and serum cortisol levels in horses with experimentally induced mild to severe airway obstruction

Abstract: Summary Background Inhaled corticosteroids are effective for the treatment of equine asthma but they induce cortisol suppression with potential side effects. Objectives To study the efficacy of ciclesonide, an inhaled corticosteroid with an improved safety profile, on lung function, clinical signs related to airway obstruction, and serum cortisol levels in asthmatic horses exposed to a mouldy hay challenge. Study design Cross‐over placebo controlled, blinded, randomised experiment. Methods Sixteen horses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0
6

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(79 citation statements)
references
References 27 publications
7
66
0
6
Order By: Relevance
“…Indeed, 19 years ago, Robinson et al found that even in horses with historical severe EA, clinical score failed to reflect low-grade airway obstruction, and suggested that without easily used, field-accessible testing equipment, lower airway disease would go underdiagnosed ( 53 ). Recently, the adapted 23-point scoring system has been shown to be the most useful in discriminating mild from severe cases, but it is unlikely to distinguish normal from subclinical disease ( 54 ), and the IDEASS scoring system has recently been described as a useful scoring system for moderate-to-severe equine asthma ( 55 ). Thus, while clinical scoring is essential to a good examination and careful research, and can potentially be useful in measuring response to treatment in the individual, it is insufficient in making the phenotypic distinction between mildly affected horses and healthy horses.…”
Section: Recommended Minimum Database For Diagnosis Of Equine Asthma mentioning
confidence: 99%
“…Indeed, 19 years ago, Robinson et al found that even in horses with historical severe EA, clinical score failed to reflect low-grade airway obstruction, and suggested that without easily used, field-accessible testing equipment, lower airway disease would go underdiagnosed ( 53 ). Recently, the adapted 23-point scoring system has been shown to be the most useful in discriminating mild from severe cases, but it is unlikely to distinguish normal from subclinical disease ( 54 ), and the IDEASS scoring system has recently been described as a useful scoring system for moderate-to-severe equine asthma ( 55 ). Thus, while clinical scoring is essential to a good examination and careful research, and can potentially be useful in measuring response to treatment in the individual, it is insufficient in making the phenotypic distinction between mildly affected horses and healthy horses.…”
Section: Recommended Minimum Database For Diagnosis Of Equine Asthma mentioning
confidence: 99%
“…The adopted "responder criterion" was based on data derived from the previously published dose finding studies, 27 in which oral dexamethasone, regarded as "gold standard", as well as ciclesonide, but not placebo administration, resulted in a greater than 30% improvement in both lung resistance (RL) and mean WCS, in the face of continued induced environmental challenge. This threshold was also confirmed in a pilot study, in which responder rate was 70.8%…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] Corticosteroids have been the subject of numerous studies related to joint disease treatment and respiratory problems. [17][18][19][20][21][22] Triamcinolone acetonide (TA), methylprednisolone acetate (MPA) and betamethasone acetate are primarily used for intra-articular injection. 23 A 2009 survey regarding joint therapy in equine practice reported that 73% of equine practitioners use TA in higher motion joints and 73% MPA in lower motion joints.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids have been the subject of numerous studies related to joint disease treatment and respiratory problems 17‐22 . Triamcinolone acetonide (TA), methylprednisolone acetate (MPA) and betamethasone acetate are primarily used for intra‐articular injection 23 .…”
Section: Discussionmentioning
confidence: 99%